2006
DOI: 10.1016/j.jdeveco.2006.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Child labor, urban proximity, and household composition

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 32 publications
3
52
1
2
Order By: Relevance
“…However, contrary to the literature that suggests a strong correlation between child labor and birth order (Emerson and Souza, 2008;Fafchamps and Wahba, 2006), mothers' accounts showed that child birth order was not determinative. A child was not forced to work if he/she did not want to or could not find a job.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, contrary to the literature that suggests a strong correlation between child labor and birth order (Emerson and Souza, 2008;Fafchamps and Wahba, 2006), mothers' accounts showed that child birth order was not determinative. A child was not forced to work if he/she did not want to or could not find a job.…”
Section: Discussioncontrasting
confidence: 75%
“…Blunch and Verner, 2000;Fafchamps and Wahba, 2006), children in Turkey are more likely to work as they get older (Dayıog˘lu, 2006;Dayıog˘lu and Assaad, 2003). In the urban child labor section of the ''Working Children 2006'' data, children in the 15-to-17 age group were more likely to work compared to children in the 12-to-14 and 6-to-11 age groups (Kıral and Tıraş , 2013).…”
Section: Child Characteristics Agementioning
confidence: 99%
“…Most international development organizations and many researchers believe fostering has negative consequences for a child's welfare outcomes (Haddad and Hoddinott 1994;UNICEF 1999;Fafchamps and Wahba 2006). This negative view of fostering is often rationalized by arguing parents reap the benefits of the practice while children shoulder the costs (see Edmonds and Pavcnik 2005 and Suri and Boozer 2007 for a related discussion of parental agency and child labor).…”
Section: Introductionmentioning
confidence: 99%
“…Third, proximity to urban areas stimulates the nonfarm activities that are instrumental to agricultural trade (which is increased by urbanization), such as transport and marketing. Recent evidence from Asia provides strong support for the effect of cities in stimulating high-return nonfarm employment in nearby rural areas (Fafchamps and Shilpi 2003;Fafchamps and Wahba 2006;Deichmann et al 2008;Thanh et al 2008).…”
Section: <>Rural Nonfarm Employmentmentioning
confidence: 99%